About Some Problems of the Methodology of the Study of State and Legal Phenomena - Vladimir Valentinovich Kozhevnikov (Polit Journal Scientific Journal of Politics, 2021)
This article is devoted to the problems of the methodology of the study of state and legal problems concerning its "core" - the methods used. Emphasizing the importance of general philosophical (universal, world outlook) methods, the emphasis is placed on the fact that, despite the criticism of Marxist-Leninism, the emergence of new research methods, in Russian jurisprudence, the dialectical-materialist method is the leading general philosophical method.